Pentingnya Keamanan Big Data Dalam Lembaga Pemerintahan Di Era Digital - Nainggolan, Natasya Salsabila; Nasution, Irwan Padli (CV. Information Technology Training Center - Indonesia (ITTC), 2023)
The changing storage techniques and data types in the digital age have prompted many organizations to look for solutions to stay ahead of the competition. The surge in data has ushered in the era of big data, where data plays a key role in strategic decision making. Big Data Technology can be used by various parties, such as large business entities/companies, SMEs and countries. Therefore, big data security is crucial, especially for government agencies to protect citizens' personal information. This article aims to highlight the importance of big data security in Indonesia's digital era. From the results of the discussion, it shows that big data security in government institutions in the digital era is very important. In Indonesia, there are regulations such as the Public Information Disclosure Law, Consumer Protection Law, Banking Law, Electronic Information and Transaction Law and regulate the protection and use of data or information. For the use of Big Data in Indonesia, it must comply with these regulations so that all data or information of residents remains safe from all criminal acts.